Model Matematika Produksi Persediaan Dengan Adanya Kerusakan Barang Dan Mempertimbangkan Pengurangan Harga Serta Penundaan Pembayaran - Desi Triana Putri; Muhammad Subhan (Journal of Mathematics UNP, 2023)
The problem about total cost of inventory that is not optimal in a company that produces its own item is something that happen and important to complete. The problem occur because the inventory control applied by the company is not effective.Deteriorating item and allowing price discount are thing that cause the total cost of  inventory is not optimal. In generally, payment that made after the item are received by the customer. However the company allowing delay in payment. The purpose of this study is to form a mathematical modelling about total cost inventory is not optimal at company with deteriorating item, price discount and delay in payment. The result of this study are a model of inventory with deteriorating item. The equation for the total cost of inventory obtained by the excistence payment delay period of replenishment item incur interest cost which cause  the total cost of inventory to be greater.